Antiproliferative effevcts of quercus infectoria galls extract and its mechanism of cell death on cervical cancer (HELA) cells - Zulkifly, Nurazila (2015)
Cancer is one of the leading causes of death worldwide. To date, most of the available therapies are detrimental and cause side effects to the patients. Therefore, patients turn to alternative treatments by utilizing herbs. Accumulating evidences have shown the wide range of therapeutics properties of Q. infectoria (QI) galls including anticancer activity. However, the mechanism of action was not well explained. Therefore, in this study, QI galls were selected for the evaluation of antiproliferative activity and mode of action. The antiproliferative activity of Q. infectoria galls aqueous extract (QIA) and ethanol extract (QIE) against cervical cancer (HeLa), ovarian cancer (Caov-3) and liver cancer (HepG-2) cell lines has been accessed by methylene blue assay. The antiproliferative activity towards normal kidney (Vero) and normal fibroblast (L929) cells were also evaluated to determine the toxic effects and selective property of the extracts. In addition, cells treated with DMSO served as negative control and cisplatin as positive control. Dose-response curve were then constructed to determine the IC50 values. Then, the mode of cell death in QI-treated cells was determined by Hoechst 33258 staining, FITC-annexin V/propidium iodide double staining and detection of apoptotic proteins. Besides, phytochemicals screening, antioxidant tests and total phenolic content analysis were done to observe the connection of bioactivity. From the results, as compared to QIE, QIA showed better antiproliferative activity with best growth inhibition towards HeLa cells (IC50 value = 13.64 ± 2.39 μg/ml) and exhibit cytoselective property. This current finding also showed that HeLa cells treated with QIA undergone apoptosis, represented by the alteration of nuclear morphology and presence of apoptotic bodies as well increased rate of apoptosis. Moreover, results have shown that QIA induced apoptosis through p53-dependant pathway. Upregulation of p53 has been observed to downregulate Bcl-2 and promoted secretion of cytochrome c, thus facilitated the execution of apoptosis through caspase-3 activation. However, no alteration of Bax expression was detected in this study. Based on the phytochemicals screening, QIA comprises of tannin, flavanoid and alkaloid. Furthermore, the antioxidant profiles showed that QIA exhibited great DPPH radical scavenging and X/XOD superoxide scavenging activities and contains high total phenolic contents. The antiproliferative activity of QIA might be contributed by the diversity of compounds that act as strong antioxidants. From this study, we can conclude that QIA exhibited its selective antiproliferative activity against HeLa cells by induction of apoptotic cell death.